O sagrado na dádiva: aproximações teóricas com a prática da solidariedade de um Irmãozinho de Jesus (da família espiritual de Charles de Foucauld) - Ferreira Neto, Lindolfo Euqueres (2009)
Marcel Mauss, the founder of French Anthropology, in order to trail Durkheim's sociological thought, investigates the phenomenon of the gift on law and morality of archaic societies as a social rule of the three obligations of giving, receiving and returning. The questioning that this work evokes is located around the issues stemmed from the relationship among the sacred, the gift and solidarity that color the life story of a member of the fraternity of Irmãozinhos de Jesus (Brothers of Jesus) (Guy Norel) belonging to the spiritual family of Charles de Foucauld. The core of the theory in question asks why the sacred obligates to the gift. Mauss searches to answer it, according to the theory of maori of Polynesian hau. According to the author, the theory of hau brings the novelty of a spiritual principle that regulates the social by believing that there is a spiritual bond among the things that have a soul and seek to return to the place of their origin through the transmission and circulation of goods, in order to return or repay, at the same level, what was taken. Thus, this perspective is a major key for the interpretation of ethnographic research about the exchange and the obligation, in accordance to the approach that is intended in this study. In turn, the theory of solidarity is within the classical French sociology. Thus, the research objective is to bring theoretical approaches between the dimension of the sacred as a strong element to the gift and the value of solidarity of the research subject. As such, this paper investigates the sacred in the course of history written in Mauss, as well as it seeks to understand the solidarity in a Brother of the Fraternity (Irmãozinho da Fraterindade), and his relationship to the socially excluded. This approach is based on qualitative methodology, anchored in the history of life (SILVA et al., 2007), and in oral history (MEIHY; HOLANDA, 2007) as reference methods, more accurate to understand a participative research, given the interaction between the researched subject and the researcher subject. In this sense, the report does not necessarily correspond to reality, because what matters is the sense that the subject gives to this reality, so that the analysis afterwards can guarantee further consideration on the individual as social. Thus, this concern is demonstrated in its socio-anthropological dimension, and its theological meaning inherent to the life of the Irmãozinho (Brother), as a valuable contribution to the reflection in the field of Sciences of Religions and its relevance for understanding the current religious phenomenon. Therefore, in the end of this research, there is a new biocentric perspective of the gift, highlighted by the ethnographic datum of the whangai hau ceremony (GODELIER, 2001), with the possibility of a conceptual expansion of the gift as a source of life given by the intersection of the sacred and solidarity, as they currently are considered only in the sphere of anthropocentric social sciences.